Preparation and Evaluation of tincture of Azadirachta indica A. Juss. Leaves - Mandal, Subash C. (Medknow Publications & Media Pvt Ltd, 1999)
Different strength of alcohol 40.50,60,70,80,90 per cent (v/v) and absolute were utilized for the preparation of tincture of azadirachta Indica A. Juss leaves by maceration for 7, 14,21 days. 60 per cent tincture produced after 21 says of maceration showed a maximum solid content of 1.425 per cent (v/v) and sowed pH 3.15. This tincture was characterized by studying is various physico-chmicla properties along wit its thin-layer chromatographic characteristics.